« Manger santé » et être en quête de plaisir pendant un cancer - Armelle Lorcy (Anthropologie & Santé)
In a context of a globalization of nutritional norms (healthy eating) disseminated in order to reduce chronic non-communicable diseases (cardiovascular diseases, cancer among others) and to promote the well-being of individuals, how do sick people live with this social order in their daily lives? This article is based on anthropological research carried out in 2012 and 2013 in a teaching hospital in Quebec about the experience of cancer chemotherapy which can lead to eating disorders. Observations and semi-structured interviews were conducted with caregivers and 21 women treated for gynecological cancer. This article has three objectives. On one hand it aims to show the internalized nutritional norm of sick people and the contrast with their behavior. On the other hand it analyzes the emotional experience of the nutritional norm and the meaning of a rival standard in oncology (eating with pleasure) in periods of stress (eating). With these data we can question the role of pleasure in nutritional education, the experience of a chronic disease and the limitations of the globalized nutritional norm.